تجليات الممارسة النقدية الثقافية في الفضاء العربي: نقد للثقافة أم نقد ثقافي؟ - قرين, نوال (University of Eloued جامعة الوادي, 2024)
يُعدُّ النقد الثقافي فعالية نقدية لها مبادئها النظرية وأسسها المنهجية، رغم أنّها تنهل من حقول معرفية مختلفة ومتباينة، في حين أنّ نقد الثقافة يقوم أساسا على اعتبار الثقافة مجالا للدراسة؛ إذ لا يتوقّف عند حدود النصوص الأدبية. وعلى ذلك وجب التقيُّد بالأطر المنهجية لكلّ مجال معرفي، لكنَّ سِعة مصطلح (الثقافة) و شموليته، جعل مجالاتها تتداخل، وعسَّر رسم حدود المجال المعرفيّ الواحد، خاصة مع بروز فكرة البينية في الدراسات النقدية المعاصرة. لذلك وجدنا من الباحثين من يجمع بين الممارسة النقدية التي يقدّمها عبد الله الغذّامي ومالك بن نبّي، وحتى نقاد الأدب من مثل مصطفى ناصف تحت رداء الدراسات الثقافية في عمومها والنقد الثقافي خاصة، بل هناك من يقرنه برايموند ويليامز غربيّا. فهل تلك الممارسات الثقافية التي قدّمها مالك بن نبي ومصطفى ناصف وعبد الله الغذّامي تدرج كلّها تحت مسمى النقد الثقافي؟ أم أنّها نقد للثقافة؟ وما حدود التماس والافتراق بينهما؟ Abstract: Cultural criticism is considered a critical activity that has its own theoretical principles and methodological foundations although it draws on distinct fields of knowledge. Cultural criticism is based mainly on considering culture as a field of study, which does not stop at the limits of literary texts. Accordingly, the methodological frameworks for each field of knowledge must be adhered to. However, the breadth and comprehensiveness of the term “culture” have led its fields to overlap, and have made the demarcation of the boundaries of a single field of knowledge difficult to draw, especially with the emergence of the idea of interdisciplinarity in contemporary critical studies. Therefore, some researchers were found to combine the critical practices presented by Abdullah Al-Ghadami and Malik bin Nabi, and even literary critics such as Mustafa Nasif, under the rubric of cultural studies in general and cultural criticism in particular, and there are even some who associate it with Raymond Williams in the West. Are those cultural practices presented by Malik Bennabi, Mustafa Nassef and Abdullah Al-Ghadami all listed under the name of cultural criticism? Or is it a criticism of culture? What are the similarities and the differences between them?
مقال. مجلة القارئ للدراسات الأدبية والنقدية. مج07 . ع.01. جامعة الوادي
Keywords: نقد الثقافة; النقد الثقافي; مالك بن نبي; مصطفى ناصف; عبد الله الغذّامي; الثقافة; criticism for culture; cultural criticism; Malik Bennabi; Mustafa Nasif; Abdullah Al-Ghadami; the culture